Implementasi Algoritma LCM (Linear Congruent Method) Pada Game Edukasi Pembelajaran Tajwid Berbasis Android - Azahra, Nur Anisa; Krisdiawan, Rio Andriyat; Priantama, Rio (Journal of Animation and Games Studies, 2025)
The field of Tajwid entails understanding the principles and methods for correctly reciting Quranic verses, focusing on precise pronunciation and articulation of each letter from its designated origin. However, Tajwid instruction at Madrasah Raudhatul Jannah continues to rely on traditional teaching methods like lectures and board writing, potentially leading to a mundane learning atmosphere and reduced student engagement. To address this, an educational game has been developed to offer interactive learning experiences, including multiple-choice quizzes and Tajwid-themed puzzles. This research seeks to create an Android-based educational Tajwid learning game using the Linear Congruent Method algorithm. The development process follows the Game Development Life Cycle approach, incorporating Unified Modeling Language for design. The resulting game application serves both as an educational tool and an entertaining platform for students. According to the User Acceptance Test (UAT), the Android-based Educational Tajwid Learning Game Application attained an 84.8% satisfaction rate, indicating its promise as a novel learning resource.